Core/shell of p-CuxO/n-ZnO nanowire arrays: Synthesis and characterization - Tamaekong N. (2017)
Copyright © 2017 American Scientific Publishers All rights reserved. Vertical aligned p-Cu x O nanowire arrays were synthesized by a simple and cost-effective thermal oxidation method. They act as cores, radial p-Cu x O core/n-ZnO shell heterostructure nanowire arrays were fabricated by thermal decomposition. Based upon the core/shell nanowire-based all oxide p-n junctions. The samples were analyzed by XRD, SEM, EDS and TEM. X-ray diffraction (XRD) analysis showed that the p-Cu x O core/n-ZnO shell nanowire consisted of phase of p-Cu x O and wurtzite phase of n-ZnO. The morphology analysis shows average diameter and length of nanowires are ~50 to 200 nm and ~10 to 30 μm, respectively. The EDS spectrum confirmed the presence of required elements in the p-Cu x O core/n-ZnO shell nanowires. It found to be Zn, O and Cu are distributed over the wires area according to a ratio of 1:2 by atomic of Cu:Zn to get good core/shell structure. The TEM characterizations show the n-ZnO shell nanoparticles are comprised of n-ZnO polycrystalline nanoparticles on the surface of p-Cu 2 O core nanowires.